SESSÃO 3Rs /SESSÃO BIOSSEGURANÇA /SESSÃO MODELOS EXPERIMENTAIS - Rocha, Maria lvaneide; Lima Neto, Abelardo Barbosa Moreira; Oliveira Freire, Jordânia Marques de; Moraes, Juliana Machado Fernandes de; Cavalcante, Géssica Soares; Moreira, rancisco José Carvalho; Moraes, Juliana Machado Fernandes de; Cavalcane, lzabel Letícia; Souza, Karla Camila Lima de; Pinto, Daniel Vieira (Ciência Animal, 2024)
Sessão 3Rs / Sessão BIOSSEGURANÇA / Sessão MODELOS EXPERIMENTAIS